2019
DOI: 10.1038/s41598-019-49447-9
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ co culturing of the sea urchin, Mespilia globulus and the coral Acropora millepora enhances early post-settlement survivorship

Abstract: Reef restoration efforts, utilising sexual coral propagation need up-scaling to have ecologically meaningful impact. Post-settlement survival bottlenecks, in part due to competitive benthic algae interactions should be addressed, to improve productivity for these initiatives. Sea urchins are keystone grazers in reef ecosystems, yet feeding behaviour of adults causes physical damage and mortality to developing coral spat. To investigate if microherbivory can be utilised for co-culture, we quantitatively assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 64 publications
1
41
1
2
Order By: Relevance
“…All data including live snail counts for each replicate aquarium at the beginning and end of all 21-day sampling intervals are available in the Supplementary Materials. While other studies have found increasing coral survival up to the highest herbivore density tested (Villanueva et al, 2013;Craggs et al, 2019), the present study clearly surpassed the maximum density required to control turf algae. Further research to optimize herbivore density in relation to system characteristics is warranted.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…All data including live snail counts for each replicate aquarium at the beginning and end of all 21-day sampling intervals are available in the Supplementary Materials. While other studies have found increasing coral survival up to the highest herbivore density tested (Villanueva et al, 2013;Craggs et al, 2019), the present study clearly surpassed the maximum density required to control turf algae. Further research to optimize herbivore density in relation to system characteristics is warranted.…”
Section: Discussioncontrasting
confidence: 76%
“…More recently, juvenile sea urchins Mespilia globulus were shown to improve growth and survival of Acropora millepora sexual recruits (Craggs et al, 2019). Multiple herbivore densities were tested, and increasing densities produced higher growth and survival up to the maximum density tested (75 urchins per 10,000 cm 2 tank surface area; Craggs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations